The Image of Publicity in Contemporary Sculptural Plastic - Ahmed Khlaif Mankhi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Current research examines the effectiveness of publicity in contemporary sculpture and the role it plays in transforming industrial products into works of art. The current research consisted of several chapters, the first section dealt with the cognitive concept of publicity and how publicity works in the daily life reality of societies. and the second section the reflections of publicity in contemporary art, which showed how publicity began in contemporary art and then turned into an artistic phenomenon that hits the artistic community by reviewing the products of the most prominent international artists The third chapter contained a set of results, including: 1-The effectiveness of commercial publicity is large, influential and continuous in contemporary art. 2-Publicity presented brands as a type of high-end product. 3- Publicity employs highly renowned artists as well as young artists. 4- The diversity of publicity between direct and indirect in contemporary artistic production.